Solution- and solid-state photophysical and stimuli-responsive behavior in conjugated monoalkoxynaphthalene–naphthalimide donor–acceptor dyads. Issue 46 (7th October 2015) - Peebles, Cameron; Wight, Christopher D.; Iverson, Brent L.
Abstract : The solution-state, solid-state and exceptional stimuli-responsive properties of a series of aromatic conjugated monoalkoxynaphthalene–naphthalimide donor–acceptor dyads is reported. Abstract : The stimuli-responsive properties of a series of aromatic conjugated monoalkoxynaphthalene–naphthalimide donor–acceptor dyads were studied. Two of the dyads, dyads1 and4, showed a difference in solid-state color between relatively faster (yellow) and slower (yellow-orange or orange) evaporation from solution, while the other dyads, dyad2 and3, only showed one color (yellow-green) for both evaporation rates. Importantly, highly solvatochromic dyad4 displayed thermochromic (orange to yellow), mechanochromic (orange to yellow) and vapochromic (yellow to orange) stimuli-responsive behavior in the solid-state with repeatable cycles of color changing. Structural and spectroscopic studies indicated that the stimuli-responsive behavior of dyad4 is the result of a 180° molecular rotation wherein the thermodynamically more stable head-to-head stacked orange crystalline solid interconverts with a head-to-tail stacked soft-crystalline yellow mesophase. The thermochromic transition of4 from a presumably more stable crystalline state (orange) to a metastable soft crystalline mesophase state (yellow) that persists at room temperature unless exposed to solvent vapor is particularly noteworthy.